A novel heat driven trigeneration system - Alnuaimi, Ahmed (2019)
Waste heat can be utilised for conversion of into electricity. Organic Rankine Cycles (ORC) can provide a suitable solution that can convert thermal energy at low temperatures to electricity and can play an important role to decreasing emissions as well as improving energy efficiency for processes such as food and drink production. The project aims to design/optimise and construct a small-scale prototype waste heat-driven combined Moist Airflow System (MAS) - trigeneration system, suitable for sustainable heating/cooling and electricity generation at a reduced cost for the process industries including food and drink manufacturing. The models of two sub-cycles (power and cooling) are developed using the Engineering Equation Solver (EES) program under the following working conditions: generator temperature